A qualitative study of the reasons for low patient safety incident reporting among Indonesian nurses - Bayu Anggileo Pramesona; Asep Sukohar; Surasak Taneepanichskul; M Fauzan Abdillah Rasyid (Associação Brasileira de Enfermagem, 2023)
ABSTRACT Objectives: to investigate the reasons for low patient safety incident reporting among Indonesian nurses. Methods: this qualitative case study was conducted among 15 clinical nurses selected purposively from a public hospital in Lampung, Indonesia. Interview guidelines were used for data collection through face-to-face in-depth interviews in July 2022. The thematic approach was used to analyze the data. Results: in this present study, seven themes emerged (1) Understanding incident reporting; (2) The culture; (3) Consequences of reporting; (4) Socialization and training; (5) Facilities; (6) Feedback; and (7) Rewards and punishments. Final Considerations: these findings should be considered challenges for the patient safety committee and hospital management to increase patient safety incident reporting, particularly among nurses in the hospital.